2010
DOI: 10.1111/j.1365-2850.2010.01587.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychotropic medication adherence in correctional facilities: a review of the literature

Abstract: Despite the high percentage of incarcerated persons with mental illness, surprisingly little is known about effective ways to increase psychotropic medication adherence in prison and upon release. Currently, there are limited definitive data regarding psychotropic medication adherence patterns among incarcerated persons, and the data that exist often miss specific information on changes in behaviour, symptom management and adherence patterns over the length of a person's sentence, which has implications for po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 42 publications
(51 reference statements)
0
8
0
Order By: Relevance
“…Given that the prison population has a high rate of psychiatric problems (Fazel et al, ; Fazel & Seewald, ) and shows low medication adherence (Mills et al, ; Shelton et al, ), and that these two variables are in turn associated with poorer patient health and increased health costs, our results are highly encouraging in terms of promoting prisoner mental health. Indeed, they suggest that in the prison context an easy‐to‐apply intervention for improving treatment adherence can, as various authors have suggested (Fazel & Seewald, ; Shelton et al, ), help to prevent treatment dropout and improve prisoners' health. Our follow‐up period was not, however, long enough to determine the extent to which improvement in treatment adherence was sustained and effective in reducing the number and duration of hospital admissions and preventing relapses.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…Given that the prison population has a high rate of psychiatric problems (Fazel et al, ; Fazel & Seewald, ) and shows low medication adherence (Mills et al, ; Shelton et al, ), and that these two variables are in turn associated with poorer patient health and increased health costs, our results are highly encouraging in terms of promoting prisoner mental health. Indeed, they suggest that in the prison context an easy‐to‐apply intervention for improving treatment adherence can, as various authors have suggested (Fazel & Seewald, ; Shelton et al, ), help to prevent treatment dropout and improve prisoners' health. Our follow‐up period was not, however, long enough to determine the extent to which improvement in treatment adherence was sustained and effective in reducing the number and duration of hospital admissions and preventing relapses.…”
Section: Discussionmentioning
confidence: 70%
“…Given that the prison population has a high rate of psychiatric problems (Fazel et al, 2016;Fazel & Seewald, 2012) and shows low medication adherence (Mills et al, 2011;Shelton et al, 2010), and that these two variables are in turn associated with poorer patient health and increased health costs, our results are highly encouraging in terms of promoting prisoner mental health. Indeed, they suggest that in the prison context an easy-to-apply intervention 2010), help to prevent treatment dropout and improve prisoners' health.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Despite the substantial amount of research examining the issue of psychiatric medication nonadherence, our knowledge about why justice-involved individuals do not adhere to their psychiatric medications as prescribed is still very limited, especially among those under community supervision (Shelton, Ehret, Wakai, Kapetanovic, & Moran, 2010). The few studies that have examined psychiatric medication adherence among a justice-involved population have mainly focused on prisoners, with only one study focusing on parolees (Baillargeon, 2000; Gray, Bressington, Lathlean, & Mills, 2008; Shelton et al, 2010).…”
Section: Introductionmentioning
confidence: 99%